Análise da relação filogenética entre Triatoma carcavalloi Jurberg, Rocha; Lent, 1998; Triatoma circummaculata Stal, 1859; Triatoma klugi Carcavallo, Jurberg, Lent; Galvão, 2001 e Triatoma rubrovaria Blanchard, 1843 (Hemiptera, Reduviidae) baseada no sequenciamento de genes do DNA mitocondrial e nuclear - Rocha, Cláudia Solano [UNESP] (2012)
The subfamily Triatominae comprises 146 species grouped in 18 genera and five tribes. The genus Triatoma is the most representative subfamily with 80 described species, which are grouped into eight complex and eight subcomplexes and this classification being based primarily on morphological characteristics. Triatoma rubravaria is considered an important vector in the transmission of Chagas disease in the state of Rio Grande do Sul since it was detected an increase of their capture and meetings colonies household after the program to combat of T. infestans. T. rubrovaria is found in groves and crevices of rocky areas within T. carcavalloi, T. circummaculata and T.klugi, which show morphological similarities. Molecular markers belonging to the nuclear DNA, as the internal transcribed spacers (ITS) have more rapid evolution, establishing recent relationships while the large ribosomal subunit 28S (D2), being well maintained, allows establishing the relationship between distantly related organisms. Mitochondrial markers (Cytochrome B - CytB and Cytochrome Oxidase I - COI) present a rate of change ten times faster than those presented by nuclear DNA, and are therefore useful for establishing phylogenetic relationships between organisms that diverged recently. A Bayesian analysis using mtDNA sequences belonging to (CytB and COI) reaffirmed the positioning of the species and indicates subcomplex rubrovaria and indicates T. carcavalloi as sister species from the group of T. klugi + T. rubrovaria + T. circummaculata. A Bayesian analysis of six populations of T. rubrovaria showed the population collected in Canguçu isolated from the others, suggesting that they are cryptic species.